Identifying early warning indicators for real estate-related banking crises - Stijn Ferrari; Mara Pirovano; Wanda Cornacchia (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2015)
This Occasional Paper presents a formal statistical evaluation of potential early warning indicators for real estate-related banking crises. Relying on data on real estate-related banking crises for 25 EU countries, a signalling approach is applied in both a non-parametric and a parametric (discrete choice) setting. Such an analysis evaluates the predictive power of potential early warning indicators on the basis of the trade-off between correctly predicting upcoming crisis events and issuing false alarms. The results in this paper provide an analytical underpinning for decision-making based on guided discretion with regard to the activation of macro-prudential instruments targeted to the real estate sector. After the publication of the ESRB Handbook and the Occasional Paper on the countercyclical capital buffer, it represents a next step in the ESRB's work on the operationalisation of macroprudential policy in the banking sector. This Occasional Paper highlights the important role of both real estate price variables and credit developments in predicting real estate-related banking crises. The results indicate that, in addition to cyclical developments in these variables, it is crucial to monitor the structural dimension of real estate prices and credit. In multivariate settings macroeconomic and market variables such as the inflation rate and short-term interest rates may add to the early warning performance of these variables. Overall, the findings indicate that combining multiple variables improves early warning signalling performance compared with assessing each indicator separately, both in the non-parametric and the parametric approach. Combinations of the abovementioned indicators lead to lower probabilities of missing crises while at the same time not issuing too many false alarms. In addition to EU level, they also perform relatively well at individual country level. Even though the best performing indicators have relatively good signalling abilities at the individual country level, national authorities are encouraged to perform their own complementary analyses in a broader framework of systemic risk detection, which augments potential early warning indicators and methods with other relevant inputs and expert judgement.
Keywords: G21; G18; E58; 330; early warning indicators; real estate; banking crises